DataNet: linking multi-faceted building energy datasets for effective performance analysis at scale - Hye-Gi Kim; Hyery Shin; Han-Gyeong Chu; Dong Hyuk Yi; Sang-Lin Park; Doosung Kim; Hyunwoo Lim; Sungmin Yoon; Eui-Jong Kim; Jaewan Joe; Sunsook Kim; Hyeunguk Ahn; et al. (Energy and Buildings, 2026)

Hydramethylnon induces synergistic toxicity of pyrethroid mixtures in human lung epithelial cells - Hye-Jin Jeong; Hye-In Park; Tae-Rim Im; Ju-Hui Im; Seung Min Choi; Chang-Ik Choi; Myungwon Seo; Yong Joo Park (Toxicological Research, 2026)

Environment-responsive phase transformation of Ni-modified cobalt phosphate aerogels for durable hydrogen evolution in freshwater and seawater - Younghun Kim; Sang-Hyun Kim; Jiseung Kim; Wonjun Lee; Hyun Jee Heo; In Hye Kwak; Vinayak G. Parale; Hyung-Ho Park (Desalination, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Hydramethylnon-induced autophagy and apoptosis in human bronchial epithelial cells by homeostatic changes - Yeon-Ho Kang; Sou Hyun Kim; Hye-Jin Jeong; Ah-Yoon Song; Hye-In Park; Eun-Hye Kim; Young-Suk Jung; Yong Joo Park (Toxicology, 2026)

Anti-inflammatory effect of a Capsosiphon fulvescens (Chlorophyta) extract obtained by subcritical water extraction on lipopolysaccharide-induced RAW 264.7 cells - Ju-Hye Im; Su-mi Park; Yu-Jin Heo; Mi-Kyung Lee; Hae-In Lee (Journal of Applied Phycology, 2026)

Future variability in groundwater-surface water interactions: Implications for streamflow and its components using SWAT-MODFLOW 6 and CMIP 6 projections - Suh-Ho Lee; Hye-Ji Kim; In-Hee Cho; Seong-Sun Lee; Hyemin Park; Youn-Tae Kim; MoonSu Kim; Kang-Kun Lee (Journal of Hydrology, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Ubiquitin-Specific Protease 20 Promotes CCCP-Induced Mitophagy Through Deubiquitination and Stabilization of Serine/Threonine Protein Kinase PINK1 - Ga Hyun Park; Hye In Park; Donghyuk Shin; Kwang Chul Chung (Journal of Molecular Neuroscience, 2025)

Genetic mapping of tomato mutants using InDel markers between S. pimpinellifolium and two S. lycopersicum cultivars - Smita Mirsyad Warsadiharja; Shandra Amarillis; Jung Heo; Seunghye Park; Hye-yeong Kang; Yong Jun Kim; Junwoo Lee; Kang Il Cha; Eun Song Lee; Ji In Jang; A-ra Joh; Keunhwa Kim; et al. (Plant Biotechnology Reports, 2025)

First report of Erysiphe lonicerae causing powdery mildew on goldflame honeysuckle (Lonicera × heckrottii) in Korea - Lamiya Abasova; In-Young Choi; Hye-Ryeong Jang; Ji-Hyun Park; Hyeon-Dong Shin (Journal of Plant Pathology, 2025)

Seasonal and spatial distributions of polycyclic aromatic hydrocarbons in surface water of the Taehwa River in the largest industrial city in South Korea - In-Gyu Cho; Hye-Ok Kwon; Sung-Hee Seo; Joo-Yeon Oh; Eun-Jeong Park; Sung-Deuk Choi (Environmental Monitoring and Assessment, 2025)

Assessment of mechanisms and efficiencies for Mn decrease at unit processes in passive treatment facilities for mine drainage - Hye-Lim Kwon; Duk-Min Kim; Seong-Sook Park; Ji-Hye Hong; Ju-In Ko (Environmental Geochemistry and Health, 2025)

A novel mechanistic model for diagnosing the general health status of kimchi cabbage using the discrete-pixel data - Sang-Deok Lee; You Jin Lim; Kyung-Hwan Yeo; Oak-Jin Lee; Yun-Soo Choi; Gyu Hyeon Park; Hyejin Lee; Hyo In Yoon; Taeyang Kim; Ji-Hye Moon (Computers and Electronics in Agriculture, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Physicochemical characterization and in vivo assessment of novel apixaban-loaded polymeric nano-aggregates - Fakhar ud Din; Hye In Lee; Jung Suk Kim; Mi Ran Woo; Seunghyun Cheon; Seonghyeon Park; Sanghyun Woo; Sung Giu Jin; Han-Gon Choi (Journal of Pharmaceutical Investigation, 2025)

Estimation of BPA, BPS, and BPF exposure levels in the general Korean population using the physiologically-based toxicokinetic model and human urinary biomonitoring for risk assessment - Min-Ju Kim; Yong-Kook Kwon; Hyung-Jun Kim; Dong-Gyun Han; In-Soo Yoon; Seungyoung Park; Gunyoung Lee; Hye Young Lee (International Journal of Hygiene and Environmental Health, 2025)

Development of a novel apixaban-loaded solid self-emulsifying drug delivery system for oral administration: physicochemical characterization and pharmacokinetics in rats - Hye In Lee; Mi Ran Woo; Fakhar ud Din; Jung Suk Kim; Seunghyun Cheon; Seonghyeon Park; Sanghyun Woo; Sung Giu Jin; Han-Gon Choi (Journal of Pharmaceutical Investigation, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

Salinity alternation with dark treatment enhances the gel quality and quantity of carrageenan in a red alga, Chondrus crispus - Hye-In Song; Ji-Sook Park; Jang K. Kim (Aquaculture, 2025)

Integrative assessment of mixture toxicity of household chemicals using the toxic unit approach and mode of action - Hye-Jin Jeong; Yeon-Ho Kang; Ah-Yoon Song; Hye-In Park; Myungwon Seo; Yong Joo Park (Toxicology, 2025)

Conjugated polymer of Multi-arm-PEG and dimethylsiloxane (CPMD) for the effective transdermal delivery of deoxycholic acid for fat reduction - Hwajun Jeong; Hye-Lin Kim; Harim Kim; Min-Suk Lee; Jae-Min Cho; Chan Lee Park; Hyo In Kim; Jinbong Park; Dokyoung Kim (Chemical Engineering Journal, 2025)

Direct aluminate precipitation technique with a phase transformation strategy for selective lithium extraction from Uyuni brine - Hee Seo Kim; Yong Jae Suh; Dae-Woo Kim; Heeji Yoo; Hye-Jin Hong; In-Su Park (Chemical Engineering Journal, 2025)

Spatial distributions and source identification of PCDD/Fs and PCBs in soils and pine needles in the multi-industrial city of Ulsan, South Korea - Hye-Kyung Cho; Sanjenbam Nirmala Khuman; In-Gyu Cho; Min-Kyu Park; Sung-Deuk Choi (Chemosphere, 2024)

Dexamethasone nanocrystals-embedded hydroxypropyl methylcellulose hydrogel increases cochlear delivery and attenuates hearing loss following intratympanic injection - Min Young Jeong; Subin Kim; Hye Rim Kim; Jiae Jeon; Seong Su Won; Keum-Jin Yang; Jun Soo Park; In Gyu Yang; Dong Geon Lee; Jin Hyuk Myung; Yoon-Gyoon Kim; Sung Giu Jin; et al. (Carbohydrate Polymers, 2024)

A new quantitative method to validate the expression of homoeologous genes in polyploids - Keunhwa Kim; Eun Song Lee; Smita Mirsyad Warsadiharja; Junwoo Lee; Hye-yeong Kang; Ji In Jang; Yu Seon Chae; Soon Ju Park (Plant Biotechnology Reports, 2024)

Synergistic effects of multi-dimensionality in an aerogel for lithium-ion battery anodes with an enhanced capacitive contribution - Younghun Kim; Young Hwan Kim; Vinayak G. Parale; Sang-Hyun Kim; In Hye Kwak; Hyung-Ho Park (Chemical Engineering Journal, 2024)

Establishment of a small-cell lung cancer (SCLC) mouse model using enhanced cancer stem-cell-functioning 3D SCLC spheroids - Yong Hun Jung; In Kyoung Kim; So Young Eom; Hyunsoo Kim; Kyungwon Park; Seok Chung; Sang Haak Lee; Chang Dong Yeo; Hye Joung Kim; Hye Seon Kang (Molecular & Cellular Toxicology, 2024)

T cell receptor clonotype in tumor microenvironment contributes to intratumoral signaling network in patients with colorectal cancer - In Hye Song; Seung-been Lee; Byung-Kwan Jeong; Jungwook Park; Honggeun Kim; GunHee Lee; Su Min Cha; Heejae Lee; Gyungyub Gong; Nak-Jung Kwon; Hee Jin Lee (Immunologic Research, 2024)

Nano-Sized rGO-Encapsulated TiO2 Nanowire-Filled PDMS cone type dielectric elastomer actuator operating at low applied electric field - Jin Sung Seo; Kyoung Tae Park; Su Min Oh; Hye In Kang; KiJong Kim; Sung-Hyeon Baeck; Sang Eun Shim; Yingjie Qian (Chemical Engineering Journal, 2024)

Exploring pharmacokinetics and herb-drug interactions of an herbal extract mixture derived from Poria cocos and Morus alba L. - So Yeong Yun; Jeong In Seo; Sang Zin Choi; Ja Young Ryu; Ah Yeon Park; Han Gon Choi; Hye Hyun Yoo (Journal of Pharmaceutical Investigation, 2024)

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

Estimation of the electrical conductivity of saturated paste from soil–water extracts of coastal saline paddy soils using random forest and multiple regression models - Hyun-Jin Park; Nuri Baek; Bo-Seong Seo; Young-Jae Jeong; Hye In Yang; Se-In Lee; Kwang-Sik Yoon; Han-Yong Kim; Woo-Jung Choi (Journal of Soils and Sediments, 2024)

Considering the Chemical Components of Particulate Matter 2.5 for Assessing Its Health Risks to Residents near the Ansan/Siheung and Ulsan Industrial Complexes - Ji-Yun Jung; Shin-Young Park; Jeong-In Jeon; Hye-Won Lee; Sung-Won Yoon; Cheol-Min Lee (Water, Air, & Soil Pollution, 2024)

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Patterns of δ15N in forest soils and tree foliage and rings between climate zones in relation to atmospheric nitrogen deposition: A review - Woo-Jung Choi; Hyun-Jin Park; Nuri Baek; Hye In Yang; Jin-Hyeob Kwak; Sun-Il Lee; Seo-Woo Park; Eun-Seo Shin; Sang-Sun Lim (Science of The Total Environment, 2023)

Efficient MAPbI3-based perovskite solar cells exceeding 21% efficiency via aging treatment - Dae Woo Kim; Young Wook Noh; Jongmin Han; Hye Seung Kim; Chung Hyeon Jang; Ji A. Hong; Sangmi Park; Min Hyeong Lee; Ye In Kim; Myoung Hoon Song (Chemical Engineering Journal, 2023)

Led-mediated instantaneous pore formation in membranes driven by structural transformation and deprotonation of phospholipids - Hui Bang Cho; Hye Jin Kim; Hye-Ryoung Kim; Sujeong Lee; Ji-In Park; Keun-Hong Park (Chemical Engineering Journal, 2023)

Adsorptive recovery of rare earth elements from aqueous solution by citric acid crosslinked carboxymethylated cellulose nanofibril aerogel - Hee Seo Kim; Dae-Woo Kim; In-Su Park; Hye-Jin Hong (Journal of Cleaner Production, 2023)

Sargassum horneri and Ascophyllum nodosum extracts enhance thermal tolerance and antioxidant activity of Neopyropia yezoensis - Sol Han; Hye-In Song; Ji-Sook Park; Youn-Jung Kim; Schery Umanzor; Charles Yarish; Jang K. Kim (Journal of Applied Phycology, 2023)

Identification of novel missense mutation related with non-syndromic sensorineural deafness, DFNA11 in korean family by NGS - Ye-Ri Kim; Hye-Min Kim; Byeonghyeon Lee; Jeong-In Baek; Kyu-Yup Lee; Hong-Joon Park; Un-Kyung Kim (Genes & Genomics, 2023)

Double-blind randomized placebo-controlled study of the efficacy and safety of hair loss prevention shampoo containing salicylic acid, panthenol, and niacinamide in alopecia patients - Hee-Taek Kim; Hye-Su Park; Yong-Min Kim; In-Chul Lee; Sang-Jun Lee; Jae-Suk Choi (Toxicology and Environmental Health Sciences, 2022)

PKC-β modulates Ca2+ mobilization through Stim1 phosphorylation - Hye-Jin Song; In-Sook Jeon; Seung Ryul Kim; Kwan Sik Park; Jae-Won Soh; Kwang Youl Lee; Jae-Cheon Shin; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2022)
Background Calcium ions play a pivotal role in cell proliferation, differentiation, and migration. Under basal conditions, the calcium level is tightly regulated; however, cellular activation by growth factors increase the ion level through calcium pumps in the plasma membrane and endoplasmic reticulum for calcium signaling. Orai1 is a major calcium channel in the cell membrane of non-excitable cells, and its activity depends on the stromal interaction molecule 1 (Stim1). Several groups reported that the store-operated calcium entry (SOCE) can be modulated through phosphorylation of Stim1 by protein kinases such as extracellular signal-regulated kinase (ERK), protein kinase A (PKA), and p21-activated kinase (PAK). PKC is a protein kinase that is activated by calcium and diacylglycerol (DAG), but it remains unclear what role activated PKC plays in controlling the intracellular calcium pool. Objectives Here, we investigated whether PKC-β controls intracellular calcium dynamics through Stim1. Methods Several biochemical methods such as immune-precipitation, site directed mutagenesis, in vitro kinase assay were employed to investigate PKC interaction with and phosphorylation of Stim1. Intracellular calcium mobilization, via Stim1 mediated SOCE channel, were studied using in the presence of PKC activator or inhibitor under a confocal microscope. Results Our data demonstrate that PKC interacts with and phosphorylates Stim1 in vitro. phosphorylation of Stim1 at its C-terminal end appears to be important in the regulation of SOCE activity in HEK293 and HeLa cells. Additionally, transient intracellular calcium mobilization assays demonstrate that the SOCE activity was inhibited by PKC activators or activated by PKC inhibitors. Conclusion In sum, our data suggest a repressive role of PKC in regulating calcium entry through SOCE.

Land use types with different fertilization management affected isotope ratios of bulk and water-extractable C and N of soils in an intensive agricultural area - Young-Jae Jeong; Hyun-Jin Park; Byeong-Jun Jeon; Bo-Seong Seo; Nuri Baek; Hye In Yang; Jin-Hyeob Kwak; Sang-Mo Lee; Woo-Jung Choi (Journal of Soils and Sediments, 2022)

Overexpression of Arabidopsis thaliana blue-light inhibitor of cryptochromes 1 gene alters plant architecture in soybean - Hyun Suk Cho; Yoon Jeong Lee; Hye Jeong Kim; Moon-Young Park; Wan Woo Yeom; Ji Hyeon Song; In Ah Kim; Seong-Hyeon Kim; Jeong-Il Kim; Young-Soo Chung (Plant Biotechnology Reports, 2021)

Temporal variation of sulfate concentration in PM2.5 and major factors enhancing sulfate concentration in the atmosphere of Seoul, Korea - Na Kyung Kim; In Sun Kim; In Ho Song; Seung Myung Park; Hyung Bae Lim; Yong Pyo Kim; Hye Jung Shin; Ji Yi Lee (Air Quality, Atmosphere & Health, 2021)

Natural hybridization between transgenic and wild soybean genotypes - Do Young Kim; Jin Ho Heo; In Soon Pack; Jung-Ho Park; Min Shik Um; Hye Jin Kim; Kee Woong Park; Kyong-Hee Nam; Sung Duk Oh; Jae Kwang Kim; Ju Seok Seo; Chang-Gi Kim (Plant Biotechnology Reports, 2021)

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

T cell receptor repertoires of ex vivo–expanded tumor-infiltrating lymphocytes from breast cancer patients - In Ah Park; Hajar Rajaei; Young-Ae Kim; Hyeonjin Lee; Heejae Lee; Jeong-Han Seo; Sun-Hee Heo; In Hye Song; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2020)

Biomass, chemical composition, and microbial decomposability of rice root and straw produced under co-elevated CO2 and temperature - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Kwang-Seung Lee; Hye In Yang; Han-Yong Kim; Sang-Mo Lee; Woo-Jung Choi (Biology and Fertility of Soils, 2020)

Land-use type, and land management and disturbance affect soil δ15N: a review - Woo-Jung Choi; Jin-Hyeob Kwak; Hyun-Jin Park; Hye In Yang; Se-In Park; Zhihong Xu; Sang-Mo Lee; Sang-Sun Lim; Scott X. Chang (Journal of Soils and Sediments, 2020)

De novo assembly and characterization of transcriptome in the medicinal plant Euphorbia jolkini - Neha Samir Roy; In-hye Lee; Jung-A Kim; Rahul Vasudeo Ramekar; Kyong-Cheul Park; Nam-il Park; Joo-Hong Yeo; Ik-Young Choi; Soonok Kim (Genes & Genomics, 2020)

Retained or altered expression of major histocompatibility complex class I in patient-derived xenograft models in breast cancer - In Hye Song; Young-Ae Kim; Hyeonjin Lee; Hye Seon Park; In Ah Park; Chan Kyu Sim; Myeong Sup Lee; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2019)

Characteristics of metal contamination in paddy soils from three industrial cities in South Korea - In-Gyu Cho; Min-Kyu Park; Hye-Kyung Cho; Jin-Woo Jeon; Sung-Eun Lee; Sung-Deuk Choi (Environmental Geochemistry and Health, 2019)

The Reduction of the Global Irradiance Due to the Asian Dust Aerosols (PM10) Estimated by the Observed Data in the Dust Source Region of Erdene in Mongolia - Soon-Ung Park; Seung Jin Joo; In-Hye Lee; Jae-Won Ju (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Sorption of Pb in chemical and particle-size fractions of soils with different physico-chemical properties - Hyun-Jung Park; Hyun-Jin Park; Hye In Yang; Se-In Park; Sang-Sun Lim; Jin-Hyeob Kwak; Goon-Taek Lee; Sang-Mo Lee; Man Park; Woo-Jung Choi (Journal of Soils and Sediments, 2019)

Inoculum effect of methicillin-susceptible Staphylococcus aureus against broad-spectrum beta-lactam antibiotics - Kyoung-Ho Song; Sook-In Jung; Shinwon Lee; Sohee Park; Eu Suk Kim; Kyung-Hwa Park; Wan Beom Park; Pyoeng Gyun Choe; Young Keun Kim; Yee Gyung Kwak; Yeon-Sook Kim; Hee-Chang Jang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Comparison of the antioxidant properties and flavonols in various parts of Korean red onions by multivariate data analysis - Mi Jin Park; Da Hye Ryu; Jwa Yeong Cho; In Jong Ha; Jin Seong Moon; Young-Hwa Kang (Horticulture, Environment, and Biotechnology, 2018)

Individualized metabolic profiling stratifies pancreatic and biliary tract cancer: a useful tool for innovative screening programs and predictive strategies in healthcare - Jun Hwa Lee; Seung Eun Yu; Kyung-Hee Kim; Myung Hyun Yu; In-Hye Jeong; Jae Youl Cho; Sang-Jae Park; Woo Jin Lee; Sung-Sik Han; Tae Hyun Kim; Eun Kyung Hong; Sang Myung Woo; et al. (EPMA Journal, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Elevated CO2 concentration affected pine and oak litter chemistry and the respiration and microbial biomass of soils amended with these litters - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Hye-In Yang; Kwang-Seung Lee; Young-Han Lee; Han-Yong Kim; Woo-Jung Choi (Biology and Fertility of Soils, 2018)

Seismicity of the 2016 ML 5.8 Gyeongju earthquake and aftershocks in South Korea - Jimin Lee; Yonggyu Ryoo; Sun Cheon Park; Young Mo Ham; Jong Soo Park; Myeong Su Kim; Sang Mi Park; Hyen Geom Cho; Keun Su Lee; In Sun Kim; Hye Su Kim; Sunhee Bae (Geosciences Journal, 2018)

Whitening and anti-wrinkle activities of ferulic acid isolated from Tetragonia tetragonioides in B16F10 melanoma and CCD-986sk fibroblast cells - Hye-Jin Park; Jun-Hyo Cho; Shin-Hyub Hong; Dong-Hee Kim; Hee-Young Jung; In-Kyu Kang; Young-Je Cho (Journal of Natural Medicines, 2018)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

Sound wave affects the expression of ethylene biosynthesis-related genes through control of transcription factors RIN and HB-1 - Joo Yeol Kim; Hye Ryun Ahn; Sun Tae Kim; Cheol Woo Min; Soo In Lee; Jin A. Kim; Soo-Chul Park; Mi-Jeong Jeong (Plant Biotechnology Reports, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

LED light for in vitro and ex vitro efficient growth of economically important highbush blueberry (Vaccinium corymbosum L.) - Cao Dinh Hung; Chang-Hee Hong; Seon-Ki Kim; Kyu-Han Lee; Jea-Young Park; Min-Woo Nam; Dae-Ho Choi; Hye-In Lee (Acta Physiologiae Plantarum, 2016)

Mycobacterium avium MAV2052 protein induces apoptosis in murine macrophage cells through Toll-like receptor 4 - Kang-In Lee; Han-Gyu Choi; Yeo-Jin Son; Jake Whang; Kwangwook Kim; Heat Sal Jeon; Hye-Soo Park; Yong Woo Back; Seunga Choi; Seong-Woo Kim; Chul Hee Choi; Hwa-Jung Kim (Apoptosis, 2016)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

LC-ESI-MS/MS analysis of phosphodiesterase-5 inhibitors and their analogues in foods and dietary supplements in Korea - Ji Hye Jeong; Ji Hyun Lee; Hyung Joo Kim; Hyoung Joon Park; In Sun Hwang; Kyoung Moon Han; Chang-Yong Yoon; Sooyeul Cho; Woo Seong Kim (Food Additives & Contaminants Part B-Surveillance, 2016)

Serological surveillance studies confirm the Rift Valley fever virus free status in South Korea - Hyun Joo Kim; Jee-Yong Park; Hye-Young Jeoung; Jung-Yong Yeh; Yun-Sang Cho; Jeong-Soo Choi; Ji-Youn Lee; In-Soo Cho; Han-Sang Yoo (Tropical Animal Health and Production, 2015)

Different anti-apoptotic effects of house dust mite allergen on eosinophil apoptosis between atopic and non-atopic asthmatic subjects - In Sik Kim; Mi Ae Im; Na Rae Lee; Seung Yeop Baek; Beom Seok Park; Ayoung Gu; Da Hye Kim; Ji-Sook Lee (Molecular & Cellular Toxicology, 2015)

Protective effect of a novel herbmedicine, Hepad, on apoptosis of SH-SY5Y cells and a rat model of Parkinson’s disease - Seung Yeop Baek; Na Rae Lee; Da Hye Kim; Ayoung Gu; Seong Yeol Kim; Dae-Yong Song; Dong-Hee Kim; Hak Joo Choi; Byung-Jun Park; In Sik Kim (Molecular & Cellular Toxicology, 2015)

A novel strain of porcine epidemic diarrhea virus in Vietnamese pigs - Yong Kwan Kim; Seong-In Lim; Ji-Ae Lim; In-Soo Cho; Eun-Hye Park; Van Phan Le; Nguyen Ba Hien; Pham Ngoc Thach; Do Hai Quynh; Tran Quang Vui; Nguyen Trung Tien; Dong-Jun An (Archives of Virology, 2015)

Glycan structure and serum half-life of recombinant CTLA4Ig, an immunosuppressive agent, expressed in suspension-cultured rice cells with coexpression of human β1,4-galactosyltransferase and human CTLA4Ig - Seung Hoon Kang; Hahn Sun Jung; Song Jae Lee; Cheon Ik Park; Sang Min Lim; Heajin Park; Byung Sun Kim; Kwang Heum Na; Gyeong Jin Han; Jae Woo Bae; Hyun Joo Park; Keuk Chan Bang; et al. (Glycoconjugate Journal, 2015)

Contributions of the pollutant emission in South Korea to the aerosol concentrations and depositions in Asia - Soon-Ung Park; In-Hye Lee; Anna Choe; Seung Jin Joo (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Analysis of an ECG Record Database Reveals QT Interval Prolongation Potential of Famotidine in a Large Korean Population - Jaesuk Yun; Eun Hwangbo; Jongpill Lee; Chong-Run Chon; Peol A. Kim; In-Hye Jeong; Manyoung Park; Raewoong Park; Shin-Jung Kang; Donwoong Choi (Cardiovascular Toxicology, 2015)

Use of rhamnolipid biosurfactant for membrane biofouling prevention and cleaning - Lan Hee Kim; Yongmoon Jung; Sung-Jo Kim; Chang-Min Kim; Hye-Weon Yu; Hee-Deung Park; In S. Kim (Biofouling, 2015)

Analysis of S-locus and expression of S-alleles of self-compatible rapid-cycling Brassica oleracea ‘TO1000DH3’ - Jung Hee-Jeong; Ahmed Nasar Uddin; Park Jong-In; Thamilarasan Senthil Kumar; Kim Hye-Ran; Cho Yong-Gu; Nou Ill-Sup (Molecular Biology Reports, 2014)

Isolation and characterization of 26 novel polynucleotide microsatellites from short barbeled grunter (Hapalogenys nitens) for genetic analysis - Hye Suck An; Hee Woong Kang; Hyon Sob Han; Jung Youn Park; Jeong In Myeong; Chul Min An (Conservation Genetics Resources, 2014)

Population genetic structure of the tongue sole (Cynoglossus semilaevis) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Hee Woong Kang; Hyon Sob Han; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Population genetic structure of the sea bass (Lateolabrax japonicus) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Development of freshwater sediment management standards for organic matters, nutrients, and metals in Korea - In Ae Huh; Yong Seok Kim; Soon Ju Yu; Stella Wong; Won Sik Shin; Hye Ok Park; Ho Jeong Kim; Hyun Woo Kim (Environmental Science and Pollution Research, 2014)

Comparative genetic diversity of wild and hatchery-produced Pacific oyster (Crassostrea gigas) populations in Korea using multiplex PCR assays with nine polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Woo Jin Kim; Hyun Jeong Lim; Eun Mi Kim; Soon Gyu Byun; Young Baek Hur; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Genetic differences between wild and hatchery populations of red sea cucumber (Stichopus japonicus) inferred from microsatellite markers: implications for production and stocking programs design - Hye Suck An; Jang Wook Lee; Seong Wan Hong; Ha Neui Hong; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Genetic differences between wild and hatchery populations of Korean spotted sea bass (Lateolabrax maculatus) inferred from microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

p53 acetylation enhances Taxol-induced apoptosis in human cancer cells - Jae Hyeong Kim; Eun-Kyung Yoon; Hye-Jin Chung; Seong-Yeol Park; Kyeong-Man Hong; Chang-Hun Lee; Yeon-Su Lee; Kyungho Choi; Young Yang; Kyungtae Kim; In-Hoo Kim (Apoptosis, 2013)

Chronological changes in inflammatory cytokines immunoreactivities in the mouse hippocampus after systemic administration of high dosage of tetanus toxin - Bing Chun Yan; Joon Ha Park; In Hye Kim; Bich Na Shin; Ji Hyeon Ahn; Ki-Yeon Yoo; Deuk-Sik Lee; Myong Jo Kim; Il-Jun Kang; Moo-Ho Won (Experimental Brain Research, 2012)

A missense mutation (c.1963A<G) of the complementary component 2 (C2) gene is associated with serum Ca++ concentrations in pigs - Jae-Bong Lee; Chae-Kyoung Yoo; Eun-Ji Jung; Jung-Hye Hwang; Bo-Young Seo; Byeong-Woo Kim; Hyun-Tae Lim; Jung-Gyu Lee; In-Cheol Cho; Hee-Bok Park (Molecular Biology Reports, 2012)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

Evaluation of the toxicological properties and hepatoprotective effects of PAI-N002, a mixture of herbal extracts, in rats - Sung-Hwan Kim; Jeong-Hyeon Lim; In-Sik Shin; Changjong Moon; Soo-Hyun Park; Sung-Ho Kim; Jung-Sik Lee; Eun-Hye Kwon; Jong-Choon Kim (Molecular & Cellular Toxicology, 2010)

Sll0396 regulates transcription of the phycocyanin genes in Synechocystis sp. PCC 6803 - In-Hye Oh; Ho-San Kim; Young-Ho Chung; Young-Hye Kim; Young Mok Park (Plant Biotechnology Reports, 2010)

Isolation and structural analysis of bamylocin A, novel lipopeptide from Bacillus amyloliquefaciens LP03 having antagonistic and crude oil-emulsifying activity - Sang-Cheol Lee; Sun-Hee Kim; In-Hye Park; Soo-Yeol Chung; Yong-Lark Choi (Archives of Microbiology, 2007)

Gene Cloning, Sequencing, and Expression of an Esterase from Acinetobacter lwoffii I6C-1 - Hye Eun Kim; In Soo Lee; Joo Hwan Kim; Kyu Woong Hahn; Ul Jae Park; Hyon Soo Han; Kyeong Ryang Park (Current Microbiology, 2003)

Characterization of an extracellular flocculating substance produced by a planktonic cyanobacterium, Anabaena sp. - Chang Won Choi; Soon-Ae Yoo; In-Hye Oh; Sang Ho Park (Biotechnology Letters, 1998)